The Management of zakat distribution among Asnaf (fakir and miskin) in Penang / Nuraina Jasmin. - Jasmin, Nuraina (2019)
The zakat institution is an intermediary between payer and recipient of zakat and it plays an important role for quoting and distributing zakat efficiently. This study will review interview research on: (1) the concept of zakat distribution among asnaf fakir miskin in Penang, (2) the criteria selected by zakat management among asnaf fakir miskin in Penang, (3) the achievement by relief of asnaf fakir miskin in Penang. This qualitative method study collected data through interview research to achieve the above objectives. Based on the data from the respondent and the hand-out provided by institution Zakat Pulau Pinang (ZPP) , it is found that concept distribution among asnaf fakir miskin were implement in ZPP which is all the assistances provided depend had kifayah that are guidelines in the Zakat Pulau Pinang (ZPP). Had kifayah is the minimum rate or amount given to one asnaf. Had kifayah is the minimum level of self-determination and the level of entitlement of zakat recipients by taking into account the differences in places, times, needs and socioeconomic conditions. However, researcher tend to propose that several requirement need to acquire in criteria selection by ZPP, first must comply with the limits of kifayah (haddul kifayah) in Penang is RM1600 and below and the main must be Muslim and they will also see at least three (3) children in school. In addition, the receiver Malaysia citizen, residing in Penang at least 3 years and not receive any assistance from other agencies or insufficient are qualify the requirement.